Wavelength-Modulated Differential Photoacoustic Spectroscopy (WM-DPAS) for noninvasive early cancer detection and tissue hypoxia monitoring - Choi, Sung Soo (Sean); Mandelis, Andreas; Guo, Xinxin; Lashkari, Bahman; Kellnberger, Stephan; Ntziachristos, Vasilis (Journal of Biophotonics, 2016)
This study introduces a novel noninvasive differential photoacoustic method, Wavelength Modulated Differential Photoacoustic Spectroscopy (WM-DPAS), for noninvasive early cancer detection and continuous hypoxia monitoring through ultrasensitive measurements of hemoglobin oxygenation levels (StO2). Unlike conventional photoacoustic spectroscopy, WM-DPAS measures simultaneously two signals induced from square-wave modulated laser beams at two different wavelengths where the absorption difference between maximum deoxy- and oxy-hemoglobin is 680 nm, and minimum (zero) 808 nm (the isosbestic point). The two-wavelength measurement efficiently suppresses background, greatly enhances the signal to noise ratio and thus enables WM-DPAS to detect very small changes in total hemoglobin concentration (CHb) and oxygenation levels, thereby identifying pre-malignant tumors before they are anatomically apparent. The non-invasive nature also makes WM-DPAS the best candidate for ICU bedside hypoxia monitoring in stroke patients. Sensitivity tunability is another special feature of the technology: WM-DPAS can be tuned for different applications such as quick cancer screening and accurate StO2 quantification by selecting a pair of parameters, signal amplitude ratio and phase shift. The WM-DPAS theory has been validated with sheep blood phantom measurements.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Biosensor; Differential photoacoustic; Hypoxia; Noninvasive; Premalignant